Wacana Penguatan Pendidikan Karakter dalam Buku Teks Sejarah Indonesia - Rica Filasari (Jurnal Pendidikan Sejarah, 2020)
Textbooks are one of the sources used in history learning in class and have an important meaning in Strengthening Character Education (PPK). Although there are doubts about the extent to which the integration of the value of PPK in writing Indonesian History textbooks is because the textbooks were born earlier than PPK. This study aims to describe the PPK discourse in the Indonesian History textbook 2013 Curriculum of Senior High Schools (SMA). The research approach used is a qualitative type of critical discourse analysis model Roger Fowler et al. The main data source is in the revised edition of the High School Indonesia History textbook 2013. The research data was collected by means of documentation. While the data are analyzed with two levels, namely the micro-level which takes into account the composition of words and sentences in the text, and the macro-level that links with the history books and the value of character education. Data checking is carried out holistically, historically situated, and theoretically by observing PPK in Indonesian History textbooks. The results of this study present nationalism as the theme of character values ​​that most often appears in Indonesian History textbooks, followed by values ​​of independence, religion, integrity, and mutual cooperation. The discourse of nationalism is very dominant in almost every textbook, especially narratives about the spirit of nationalism in the process of nation and state formation.